The History of the Birth of Traditions and Conflicts over the Nabi Samuel Shrine (Israel/Palestine) - Briks, Piotr (Wydawnictwo Uniwersytetu Rzeszowskiego, 2024)
During the Crusades, the almost forgotten small Byzantine monastery of St. Samuel (4th-c.) became a key place on the map of Holy Land pilgrimages. Initially important only to Christians, the shrine quickly became a pilgrimage destination for Jews and later for Muslims. Each of these communities left an indelible mark on the traditions and customs of this holy place. During some periods, they managed to celebrate the memory of Samuel in unison, but largely the shrine was a source of conflicts or even bloody battles. In 1967, the area around Nabi Samuel was incorporated into the Israeli-Occupied Territories. Due to the rich tradition associated with the cult of the OT prophet, but even more the significance of Nabi Samuel (identified as the ancient Mizpah), the Israeli authorities have tried to make this site a memorial to Israel’s ancient history, and at the same time a tourist attraction. Since then, the actions of the authorities have provoked constant protests and unrest. As has recently been revealed, the motivations of the Israeli administration are not only religious, historical, and political, but also business-related, although this is shamefully hidden behind lofty slogans.

Niemal zapomniany, maleńki bizantyjski klasztor (z IV w.) pw. proroka Samuela stał się w okresie wypraw krzyżowych jednym z najważniejszych miejsc na pielgrzymkowej mapie Ziemi Świętej. Sanktuarium, ważne początkowo wyłącznie dla chrześcijan, z czasem stało się celem pielgrzymek żydów, a później także muzułmanów. Każda z tych wspólnot religijnych pozostawiła niezatarte piętno na tradycjach i zwyczajach tego sanktuarium. W niektórych okresach udawało się czcić pamięć proroka Samuela w miarę zgodnie, ale przeważnie sanktuarium było źródłem konfliktów, a nawet krwawych bitew. W 1967 r. obszar wokół Nabi Samuel został włączony do Terytoriów Okupowanych przez Izrael. Ze względu na bogatą tradycję związaną z kultem proroka Starego Testamentu, ale także historyczno-polityczne znaczenie Nabi Samuel (utożsamianego ze starożytnym Mizpah) izraelskie władze próbowały uczynić to miejsce pomnikiem historii Izraela, a jednocześnie atrakcją turystyczną. Od tego czasu działania władz wywoływały ciągłe protesty i niepokoje. Jak ostatnio ujawniono, motywacje administracji izraelskiej miały charakter nie tylko religijny, historyczny i polityczny, ale także biznesowy, choć fakt ten jest ze wstydem ukrywany za wzniosłymi hasłami.
Historia narodzin tradycji i konfliktów wokół sanktuarium Nabi Samuel (Izrael/Palestyna)
Keywords: Nebi Samwil; Mons Gaudii; Mount Joy; Shrines in Israel; Tomb of the Prophet Samuel; sanktuaria w Izraelu; Grób proroka Samuela